2019
DOI: 10.3389/fphar.2019.01347
|View full text |Cite|
|
Sign up to set email alerts
|

Exploiting Curcumin Synergy With Natural Products Using Quantitative Analysis of Dose–Effect Relationships in an Experimental In Vitro Model of Osteoarthritis

Abstract: Introduction: Drug combination is widely used to treat chronic inflammatory diseases. A similar strategy might be worth of interest to design plant-derived natural products to treat inflammatory conditions. Curcumin is a natural phenolic compound which shares anti-inflammatory activity with both flavocoxid, a flavonoid mixture of baicalin and catechin, and β-caryophyllene, a bicyclic sesquiterpene. The aim of this study was to investigate the synergy potential of curcumin with both flavocoxid and β-caryophylle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…For example, β-caryophyllene is a type 2 cannabinoid (CB2) receptor agonist and has been reported to inhibit α-glucosidase [ 55 , 56 ]. It also has anti-inflammatory activity in vitro and in vivo [ 57 , 58 , 59 ]. The reported immunomodulatory effects of β-caryophyllene include inhibition of microglial cells, CD4 + and CD8 + T lymphocytes, and expression of proinflammatory cytokines [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, β-caryophyllene is a type 2 cannabinoid (CB2) receptor agonist and has been reported to inhibit α-glucosidase [ 55 , 56 ]. It also has anti-inflammatory activity in vitro and in vivo [ 57 , 58 , 59 ]. The reported immunomodulatory effects of β-caryophyllene include inhibition of microglial cells, CD4 + and CD8 + T lymphocytes, and expression of proinflammatory cytokines [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…GF and EC cells were cultured in six well culture plates at a density of 2.5 × 10 5 cells/well and were challenged with LPS (2 µg/mL; Escherichia coli serotype 055:B5; Sigma-Aldric, Milan, Italy) alone or with BCP (Sanherb Biotech Inc., China) at the dose of 10 µg/mL. A previous study showed that this dose represents the IC50 of the biomolecule at least in the experimental paradigm of LPS stimulated human chondrocytes and considering IL-1β as readout of this bioassay [18]. Furthermore, a set of LPS challenged GF and EC cells were treated with BCP (10 µg/mL) and AM630 (100 nM; Sigma-Aldric, Milan, Italy), an antagonist of the CB2 receptor.…”
Section: Treatments Of Cellsmentioning
confidence: 99%
“…For evaluating the effect of ratio of DRE and RAE in combination (5 mg/ml) on α‐glucosidase inhibition, the DRE and RAE were combined by the ratio of 3:1, 2:1, 1:1, 1:2, and 1:3, and the IC 50 values were measured as an indicator for judgment. Then, the analysis was based on the median‐effect principle (Chou‐Talalay) (Chou & Talalay, 1984; D'Ascola et al., 2019), and the median‐effect equation was presented as f a / f u = ( D / D m ) m , where D is the dose; f a and f u are the fractions of effective and ineffective part by the dose D ; D m is the dose that produces the median effect; and m represents the Hill‐type coefficient of the dose–response curve. From this, the median‐effect plot was generated.…”
Section: Methodsmentioning
confidence: 99%